Keberlanjutan Program Corporate Social Responsibility (CSR) Pengelolaan Sampah Organik dengan Black Soldier Fly (BSF) oleh PT. Pertamina Gas di Desa Penatarsewu - Nadiah Nur Hana; Arimurti Kriswibowo (Administratio, 2022)
Increasing population growth can be a problem not only for social and economic aspects but also for the environment. The impact of an increasing population on the environment causes an increase in the amount of waste. Organic waste generation has a higher percentage than other types of waste, both nationally and specifically in Sidoarjo Regency. One of the innovations in reducing organic waste is by using Black Soldier Fly (BSF) larvae. In dealing with waste problems, not only the government but also the active participation of the community and the private sector are needed. PT. Pertamina Gas is one of the BUMN initiated the innovation of the Corporate Social Responsibility (CSR) program for organic waste management using BSF to empower the community in Penatarsewu Village, Tanggulangin District, Sidoarjo Regency. This study aims to analyze the sustainability of the CSR program of PT. Pertamina Gas manages organic waste using BSF in Penatarsewu Village. The research method used in this research is a qualitative research method. The data in this study was collected through observation, interviews, and documentation. The results showed that the CSR program of PT. Pertamina Gas waste management with BSF is quite sustainable. From six aspects, there are three aspects that show good results, while the other three aspects require review and improvement to support the sustainability of the program.